2014
DOI: 10.1039/c4py00234b
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular covalently cross-linked quaternary ammonium poly(ether ether ketone) with polybenzimidazole for anhydrous high temperature proton exchange membranes

Abstract: The phosphoric acid doped quaternary ammonium poly(ether ether ketone) membranes cross-linked with PBI showed improved performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…After reaction, the H atom in eNHe of BIm was replaced by a carbon atom, giving rise to benzyl benzimidazole (BBIm), in which both the binding energy of nitrogen in tertiary amine (R 3 N) and imine presented a slight increase in comparison to BIm (Fig. 3b) [34]. The N 1s signal of the other model reaction product, dibenzyl benzimidazolium chloride (DBBImCl), should appear in an even higher binding energy due to the positive charge of imidazolium (Fig.…”
Section: Structure Analysis Of Pbi-c-pvbc Membranementioning
confidence: 98%
See 1 more Smart Citation
“…After reaction, the H atom in eNHe of BIm was replaced by a carbon atom, giving rise to benzyl benzimidazole (BBIm), in which both the binding energy of nitrogen in tertiary amine (R 3 N) and imine presented a slight increase in comparison to BIm (Fig. 3b) [34]. The N 1s signal of the other model reaction product, dibenzyl benzimidazolium chloride (DBBImCl), should appear in an even higher binding energy due to the positive charge of imidazolium (Fig.…”
Section: Structure Analysis Of Pbi-c-pvbc Membranementioning
confidence: 98%
“…Recently, Yang et al [33] and Zhang et al [34] found that an S N 2 type reaction could occur between eCH 2 Cl group of PVBC and amine group (eNHe) of PBI at elevated temperature without the use of highly flammable hydride (e.g., LiH and NaH). However, they did not mention whether the other N containing group, imine (¼Ne), will react with eCH 2 Cl group.…”
Section: Structure Analysis Of Pbi-c-pvbc Membranementioning
confidence: 98%
“…After completely drying the synthesized PAES block copolymer, a bromination reaction was performed using NBS and BPO to synthesize Br-PAES. Since bromination proceeds through sensitive radical reactions, it was taken place under nitrogen atmosphere [20]. By following this procedure, various polymers with different degrees of bromination reaction were synthesized by controlling the equivalent of NBS.…”
Section: H-nmrmentioning
confidence: 99%
“…[1][2][3] Especially, as one of the most promising class of heat-resistant engineering polymers, poly(ether ether ketone) (PEEK) is widely applied due to the outstanding properties, such as thermal stability and chemical stability. 4,5 However, the availability of such polymers is limited to a certain extent for a variety of reasons, such as the relatively low glass transition temperature (T g ) and poor solubility. Despite of much research efforts dedicated to the structural modification, 6-8 the development of a new strategy for construction of soluble and heat-resistant polymer materials through chemical polymerization is still an attractive and promising goal.…”
Section: Introductionmentioning
confidence: 99%